Catalyst‐Free Intramolecular Formal Carbon Insertion into σ‐CC Bonds: A New Approach toward Phenanthrols and Naphthols1. Issue 9 (29th January 2013) - Xia, Ying; Qu, Peiyuan; Liu, Zhenxing; Ge, Rui; Xiao, Qing; Zhang, Yan; Wang, Jianbo
<x xml:space="preserve">Abstract</x> The different reactivity of two kinds of carbonyl groups in keto aldehyde substrates has been exploited for the synthesis of phenanthrols, naphthols, and their heteroatom‐containing analogues. Key to this highly efficient and robust methodology is the catalyst‐free intramolecular formal diazo carbon insertion of N‐tosylhydrazones into keto CC bonds (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>